Anti-spike protein antibody titer at the time of breakthrough infection of SARS-CoV-2 omicron. Issue 7 (July 2022) - Adachi, Eisuke; Nagai, Etsuko; Saito, Makoto; Isobe, Masamichi; Konuma, Takaaki; Koga, Michiko; Tsutsumi, Takeya; Nannya, Yasuhito; Yotsuyanagi, Hiroshi
Abstract: By December 2021, about 80% of people over the age of 12 had been vaccinated in Japan, and almost all people were vaccinated with the mRNA vaccine. We investigated here the anti-spike protein antibody titer at the time of breakthrough infection of SARS-CoV-2 omicron. A total of 32 SARS-CoV2 omicron breakthrough infection was included in the study. The median antibody titer at breakthrough infection was 776 AU/mL overall, of which the median antibody titer of BNT162b2 vaccinated was 633 AU/mL and that of mRNA-1273 vaccinated was 9416 AU/mL. This result suggests that low levels of antibody titers 6 months after vaccination do not provide sufficient antibodies to prevent the omicron variant breakthrough infection, which may occur with a higher anti-spike antibody titer after vaccination with mRNA-1273. However, antibody titers in some patients were comparable to those immediately after the second vaccination with either mRNA vaccine.